Assessing Correlation between Peripheral Neuropathy Score and Angle of Dorsiflexion of Ankle Joint among Cases of Type-2 Diabetes Mellitus - Khanal, Laxman; Mahat, Samyog; Gautam, Prajwal; Sharma, Sanjib Kumar (Annapurna Journal of Health Sciences, 2026)
Introduction: Diabetic neuropathy, a major cause of diabetic foot, typically begins with sensory deficits and may progress to motor issues like ankle muscle weakness and reduced joint flexibility. If ankle dorsiflexion (ADF) angle correlates with neuropathy scores, it may serve as a simple, low-cost screening tool in community settings. This study aimed to assess the relationship between peripheral neuropathy scores and ADF angle in patients with Type 2 Diabetes Mellitus. Methods: This cross-sectional analytical study was conducted in the community health program among 109 adults with Type 2 DM. Neuropathy was assessed using the Symptomatic method, 10g monofilament test, and 128-Hz tuning fork. Ankle dorsiflexion was measured using a manual goniometer in the knee-extended supine position. Correlation analysis was performed to determine the relationship between neuropathy scores and ADF angle. Results: Among participants 38.5% were male, mean age was 57.7 years, and mean BMI was 28.52 kg/m². ADF angle showed significant negative correlation with symptomatic score (r = -0.216, p = 0.024), but weak, non-significant correlations with monofilament test and vibration perception time. This result supports the possibility of ADF angle as a potential screening tool to predict neuropathy in community setting among type 2 DM patients. Conclusion: A significant inverse correlation found between ADF angle and symptomatic score supports the possibility of ADF angle as a potential screening tool to predict neuropathy in community setting among type 2 DM patients.